PENERAPAN JOBSHEET PEMBUATAN DESAIN BUSANA RUMAH SECARA DIGITAL MENGGUNAKAN APLIKASI SKETCHBOOK KELAS XI SMKN 1 JABON - Salsabilla, Monica; Wahyuningsih, Urip; Rahayu, Imami Arum Tri; Nashikhah, Ma’rifatun (Jurnal Socia Akademika, 2023)
The objectives of the research include 1) Knowing the results of implementing learning to design home clothing digitally with the help of Jobsheets for class XI students at SMKN 1 Jabon. This type of research is quantitative descriptive. This research was carried out at SMKN 1 Jabon in class digital. The results of the research show that the implementation of learning to apply Jobsheets for making digital home fashion designs using the Sketchbook application has been carried out very well with a score of 94%. Meanwhile, student learning outcomes are in accordance with the application of the Jobsheet. The learning outcomes of students who got a cognitive score were an average of 83, and a psychomotor score was an average of 80,5. The results of students' classical learning calculations obtained a result of 92% which was stated to be very effective and efficient regarding student competence.